Biomechanical factors to be taken into account to prevent injuries and improve sporting performance on artificial turf - Soriano, P. P.; Belloch, S. L.; Tormo, M. C.; Turpin, J. A. P. (Journal of Human Sport & Exercise, 2009)
This article reviews existing knowledge concerning the epidemiology, instruments and regulatory criteria currently used to evaluate artificial turf soccer pitches. Recent years have seen tremendous growth in the use of artificial turf as a playing surface for sports (rugby, soccer, American football...) and the problems traditionally associated with artificial turf and its relationship with a higher percentage of injuries seem to be disappearing. The contribution of biomechanics to the development of new techniques and instruments for analysing the properties and characteristics of grass pitches has contributed towards close collaboration with the regulatory bodies of different sporting organisations to define standards and criteria that guarantee not only the safety of the sportsmen and women, but also ensure performance and entertainment. Absorption of impacts, friction and traction, abrasion and factors associated with the mobile element and its interaction with artificial turf are the properties evaluated using a wide range of methodologies and instruments. In this sense, instruments such as the "Artificial Athlete" and the "Stuttgart Skiddometer" have helped different standards (DIN, BSI, AENOR, AFNOR, FIFA...amongst others) to define criteria for the homologation of a certain artificial turf surfaces.